Портландцементний клінкер з різновидами каоліну - Дорогань, Н. О.; Свідерський, В. А.; Черняк, Л. П. (НТУ "ХПІ", 2014)
Наведено дані про залежність характеристик портландцементного клінкеру від різновиду каоліну у складі сировинної суміші. Показано можливість оптимізації складу сировинної суміші і аналізу залежності фазового складу клінкеру при застосуванні нової комп'ютерної програми. Інтенсифікація утворення С3S і С2S у клінкері при застосуванні незбагаченого лужного каоліну пов'язується як із відносно більшою концентрацією кальциту і кварцу у сировинній суміші, так і з кристалізацією у присутності більш розвиненої за рахунок польового шпату рідкої фази.

The data are given on the dependence of portlandcement clinker properties on the kaolin variety in the composition of raw mixture. It is shown that the use of kaolinеs of Ukraine in the raw mixture, which are different by genesis, degree of enrichment, and chemical and mineralogical composition is an important factor influencing the clinker properties and the processes of phase transformations during firing. It is shown a possibility of optimizing the composition of raw mixture and the analysis of dependence of the clinker phase composition using a new computer program. Intensification of C3S and C2S formation in the clinker using unenriched alkaline kaolin is associated both with the relatively higher concentration of calcite and quartz in the raw mixture, and with crystallization in the presence of more developed liquid phase due to feldspar. The achieved minimization of formation of iron-containing crystalline phases determines the possibility of increasing the clinker and cement whiteness on its basis.
Portland cement clinker with the varieties of kaolin
Keywords: сировинна суміш; портландцемент; клінкер; каолін; цементний клінкер; portland cement; clinker; kaolin; raw mixture